Implementasi Karakter Religius Dan Peduli Sosial Pada Petugas Pemadam Kebakaran(Studi Kasus Pada Anggota Petugas Pemadam Kebakaran Bpbd Kota Surakarta) - Prakoso, Rian Eko (2016)
The purpose of this study was to describe a) the implementation of the religious character of the members of the firefighters BPBDs Surakarta, b) implementation of the character of social care to the members of the firefighters BPBDs Surakarta, c) the constraints and solutions in the implementation of the religious character of the members of the firefighters BPBDs city Surakarta, d) constraints and solutions in the implementation of social care character on members of firefighters BPBDs Surakarta. This research was qualitative single case study strategy. Data collection techniques with interview, observation and documentation. Source of data in this study informants, places / events, and records / documents. Validity of the data in this study using triagulasi sources and techniques. Data was analyzed using an interactive model. Results of this study concluded that members of the firefighters BPBDs Surakarta apply religious character to pray before and after doing the work, celebrating religious holidays, has facilities used for worship, and live in harmony with other faiths. Members firefighters BPBDs Surakarta implement social care by facilitating the characters are social activities, social action, providing the facility to contribute, empathy for fellow human beings, as well as the cohesion of the community. Obstacles and solutions applied in the implementation of the religious character is a firefighter BPBDs office Surakarta not have worship space rather broad. The solution is hoped that there development and repair again. Obstacles and solutions applied in the implementation of social care is the lack of character of refugee camps for victims of natural disasters. The solution so that there are additional tents even more. Each occurrence of missing persons took a long time to overcome. The solution must be able to build an attitude of discipline, patience and vigilance. Keywords: Character, Religious, Social Care, Extinguisher, Fire Surakarta, 26 January 2016 Author Rian Eko Prakoso